Produtividade de alguns cultivares de feijão-de-vagem (Phaseolus vulgaris L) de porte baixo - Gomes Coelho , Ronaldo; Rocha Leal , Nilton; Teixeira Liberal , Mozart; B de Castro , Luiz Antônio (Revista Ceres, 2025)
This study was carried out at two experimental stations of IPEACS, at Itaguai and at Avelar, Vassouras, Rio de Janeiro in 1972 and 1973 to test the behavior of 8 snap bean cultivars in the regions Serrana and Baixada Fluminense.